Some Effects Observed in the Magnetic Fluid under the Influence of Quasi-Homogeneous Magnetic Field - Stelina, Julius; Musil, Ctibor (Communications - Scientific letters of the University of Zilina, 2010)
The effect of homogenous external magnetic fields on the created space structure of a nanoparticle distribution in a sample of magnetic fluid was studied. A grating was formed by the interference field of two crossed Ar-laser beams. The magnetic field was formed by using two electromagnets. The magnetic field oriented parallel to strips of grating does not significantly change the shape of nanoparticle grating. Perpendicular direction of magnetic field causes redistribution of the nanoparticles and in consequence of that the perpendicular nanoparticle “quasi-grating” arised.